EKSISTENSI DAN PENEGAKAN HUKUM PERBANKAN SYARIAH DI INDONESIA - Utama, Sofyan Mei (Jurnal Wawasan Yuridika, 2012)
The existence of syariah banking in Indonesia was thought about because of monetary crisis in 1997 as well as national political crisis. They had brought impact and influenced national economy. Such crisis has already given inspiration to bring up out of the alternative bank which could be developed in Indonesia, such as syariah banking. The research has shown that syariah bank can survive from monetary crisis, so the existence of syariah banking is hoped to become one of reliable banks. Nevertheless, in order to make syariah banking survive with its characteristic, the law enforcement of syariah banking requires more selective supervision of Bank Indonesia and needs to be supported by excellent human resources. Finally, syariah banking can still be trusted by society, and becomes one of alternative bank in Indonesia.Keywords: monetary crisis; syariah banking; law enforcement